Adverse Events in Patients Receiving Placebo in Phase III Trials of Biologics for Psoriasis: A Systematic Review and Meta-Analysis. Issue 1 (January 2023) - Ajenthen, Gayathri Devaraj; Egeberg, Alexander; Melgaard, Katrine Elsner; Loft, Nikolai
Background: Patients and practitioners often consider the risk of side effects when starting a treatment for psoriasis and often consult reported adverse events (AE) in studies. However, most of these AEs are unrelated to treatment and patients consider what is the risk of an event should you not start a treatment. This is what would be observed in the placebo-arm of clinical trials. Objective: To investigate the proportion of patients experiencing AEs during treatment with placebo in clinical trials. Methods: We conducted a systematic literature search using PubMed, Embase and Web of Science databases for phase 3 randomized clinical trials that registered adverse events of using placebo vs biological agents for psoriasis. The search term was " Psoriasis AND (Phase III OR Phase 3) ". Results: Of 7142 screened articles, 54 were included in the metanalysis. The pooled proportion of placebo-treated patients experiencing any AEs was .52 (95% Cl: .51 to .53) after 12 weeks and .53 (95% Cl: .50 to .55) after 16 weeks. The pooled proportion of patients with any serious AEs was .02 (95% Cl: .01 to .02) and .03 (95% Cl: .02 to .03) after 12 and 16 weeks, respectively. The most common AEs in placebo-treated patients were infections, nasopharyngitis, and headache. Conclusion: About half of the patients with moderate-to-severe psoriasis not starting an active treatment would experience disease events that would be categorized as AEs during a 12-16 weeks period.